The optic nerve and visual pathways - Christopher J. Lyons (2018)
We review the clinical examination of the optic disc and assessment of the integrity of the visual pathways: assessment of vision in the infant and child, assessment of disc size and configuration, detection of abnormalities such as cupping or disc swelling and their significance, visual field examination in the child, and the various field defects which result from pathology affecting the visual pathway anywhere along its course. Congenital anomalies of the optic disc, their systemic associations and significance are discussed. We also review the presentation of the visually impaired child, the significance of nystagmus in this context, the differential diagnosis and investigation. © 2013 Elsevier B.V.